2017
DOI: 10.1016/j.crma.2017.07.003
|View full text |Cite
|
Sign up to set email alerts
|

Newton polytopes and symmetric Grothendieck polynomials

Abstract: Symmetric Grothendieck polynomials are inhomogeneous versions of Schur polynomials that arise in combinatorial K-theory. A polynomial has saturated Newton polytope (SNP) if every lattice point in the polytope is an exponent vector. We show Newton polytopes of these Grothendieck polynomials and their homogeneous components have SNP. Moreover, the Newton polytope of each homogeneous component is a permutahedron. This addresses recent conjectures of C. Monical-N. Tokcan-A. Yong and of A. Fink-K. Mészáros-A. St. D… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2019
2019
2025
2025

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 7 publications
0
5
0
Order By: Relevance
“…We prove Conjectures 1.2 and 1.4 for Grassmannian permutations. We begin by reviewing the main result of [5]. Recall a permutation w is Grassmannian if w has exactly one descent.…”
Section: Denote By G Topmentioning
confidence: 99%
“…We prove Conjectures 1.2 and 1.4 for Grassmannian permutations. We begin by reviewing the main result of [5]. Recall a permutation w is Grassmannian if w has exactly one descent.…”
Section: Denote By G Topmentioning
confidence: 99%
“…The inflated symmetric Grothendieck polynomial indexed by λ and h is Escobar and Yong [12] showed that the symmetric Grothendieck polynomial G λ (x) has SNP and described the components of the Newton polytope associated to the homogeneous components of G λ (x). We extend the work of Escobar and Yong to G h,λ (x) and show that G h,λ (x) also has SNP.…”
Section: The Newton Polytope Of a Schur Polynomialmentioning
confidence: 99%
“…Proof. In [11], the proof that G 1,λ (x) = G λ (x) has SNP does not depend on the inflation parameter h other than in [11, Claim A], which describes the structure of Newt(G λ (x)) arising from the homogeneous components of G λ (x). Using the description of the homogeneous components of G h,λ (x) from Proposition 3.9, the rest of the proof in [11] applies to arbitrary h ∈ Z ≥1 and shows that G h,λ (x) has SNP.…”
Section: And Only If α βmentioning
confidence: 99%
See 1 more Smart Citation
“…The M-convexity of the support of G k w was conjectured in [MS17, Conjecture 5.1] and proved in [EY17] when w is a Grassmannian permutation. Conjecture 20 implies Conjecture 15 because the degree pwq homogeneous component of G w is the Schubert polynomial S w .…”
Section: Ubiquity Of Lorentzian Polynomialsmentioning
confidence: 99%